Cardiac glycosides from the roots of Streblus asper Lour. and their apoptosis-inducing activities in A549 cells. (January 2021) - Zhang, Bo-dou; Zhu, Wan-fang; Akihisa, Toshihiro; Kikuchi, Takashi; Ukiya, Motohiko; Maya, Fukuda; Xu, Jian; Liu, Wen-yuan; Feng, Feng; Zhang, Jie
Abstract: Phytochemical investigation of the roots of Streblus asper Lour. resulted in the isolation of six previously undescribed cardiac glycosides, designated 2′-de- O -methylstrebloside (1 ), cannogenol-3 α - O - β -D-gluopyranosyl-(1 → 4)-6-deoxy −2, 3-dimethoxyl- β -D-fucopyranoside (2 ), periplogenin-3- O - α -L-rhamnopyranosyl -(1 → 4)-6-deoxy- β -D-allopyranoside (3 ), 5-de- O -hydroxylstrebloside (4 ), 5 β H-16 β -hydroxylkamaloside (5 ), and 17 S, 21 R -21-hydroxylstrebloside (6 ), and three known analogues (7 –9 ). The structures were elucidated using NMR spectroscopic techniques, mass spectrometry, and comparison of the spectroscopic data with previously reported data. Compound 6 is a novel C-21 hydroxyl cardiac glycoside, its absolute configuration was established from the analysis of computational ECD calculations and NMR spectroscopic data. The effects of the cardiac glycosides on apoptosis and cytotoxicity were examined in human A549 lung cancer cells. All the compounds showed remarkable inhibitory activities, with IC50 values in the range of 0.01–6.08 μM. Furthermore, compound 3 was able to significantly inhibit A549 cell growth proliferation via the induction of apoptosis, due to the activation of caspases-3, -8 and -9 in A549 cells, as revealed by Western blot analysis. Graphical abstract: Image 1 Highlights: Six previously undescribed cardiac glycosides were isolated from Streblus asper Lour. Their structures were determined by NMR spectroscopic data and ECD calculations. The isolated compounds were screened for their in vitro cytotoxicity against human A549 lung cancer cells. An previously undescribed cardiac glycoside significantly inhibited A549 cells growth proliferation via induction of apoptosis.